2007
DOI: 10.1177/102986490701100103
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based composition in the primary school: An investigation of children's “creative” responses using the CD Rom Dance eJay

Abstract: The aim of this study was to investigate computer-based music composition using the CD Rom Dance eJay. The research questions addressed the extent to which participants adopted different strategies during the composition process, how the strategies were potentially different due to prior experience of formal instrumental music tuition (FIMT), and how the process data showed evidence of creative thinking skills in music. The design subscribed to a within-methods approach within a qualitative research paradigm w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The challenge for the research was how to research the students’ perceptions of singing as a group process. In addressing this, the research methodology draws from previous work in the field of the student perspective in music education (Mellor, 1998, 2000, 2007, 2008), and recent research which applies a reflexive methodological approach from the field of research in counselling and psychotherapy (Mellor 2009 a , 2009 b , 2010; Mellor & Tune, 2011). This introduces two key ideas for the research presented here: (i) in the use of ourselves in research and (ii) reflexivity , presented through the work of Etherington (2004).…”
Section: Research Approachmentioning
confidence: 99%
“…The challenge for the research was how to research the students’ perceptions of singing as a group process. In addressing this, the research methodology draws from previous work in the field of the student perspective in music education (Mellor, 1998, 2000, 2007, 2008), and recent research which applies a reflexive methodological approach from the field of research in counselling and psychotherapy (Mellor 2009 a , 2009 b , 2010; Mellor & Tune, 2011). This introduces two key ideas for the research presented here: (i) in the use of ourselves in research and (ii) reflexivity , presented through the work of Etherington (2004).…”
Section: Research Approachmentioning
confidence: 99%
“…However, the pattems of results obtained in this study, along with anecdotal observations during the administration phase of the MET, confirmed its suitability for use in the general population. This supplements recent efforts to study musical creativity in this population using increasingly popular computer-based compositional approaches (e.g., Mellor, 2007).…”
Section: Discussionmentioning
confidence: 82%
“…However, as new music technologies become increasingly popular, many people are now involved in amateur creative-musical production (e,g,, Mellor, 2007;Mellor, 2008;Partti & Karlsen, 2010;Ward, 2009), An increasing number of studies show the positive effects of active engagement with music on intellectual, social, and personal development (Hallam, 2010), Thus, the study of musical creativity-as a general psychological dimension-is a contemporary research topic with important implications beyond musical education concerns. Yet, a fundamental challenge to advance the research in musical creativity is its assessment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in music technology have profoundly affected the research and practice of children’s creative music-making (Gall & Breeze, 2005; Nilsson & Folkestad, 2005; Seddon & O’Neill, 2001, 2003), raising questions also about pedagogy, curriculum and ethics (Brown & Dillon, 2012; Burnard, 2007). Classroom applications using technology to compose are amply represented in the literature (Mellor, 2007; Nilsson & Folkestad, 2005), yet the ways in which technology can facilitate other facets of creative music-making, such as musical improvisation, are less explored, particularly with younger children.…”
Section: Technology Improvisation and The Miror-impro Systemmentioning
confidence: 99%